Current workflows in forage breeding scheme - Hernandez, Luis; Jauregui, Rosa (2025)
The RS-SCA scheme, adapted from Miles (2007), is applied to forage species such as Urochloa and Megathyrsus. The process begins with interspecific crosses between Urochloa ruziziensis (sexual) and apomictic species like U. brizantha and U. decumbens. The goal is to introduce genetic variability and combine desirable traits. From these crosses, a synthetic population of sexual clones is formed and selected based on testcross progeny performance and resistance to spittlebug. Sexual clones with high SCA are recombined in subsequent cycles to improve the population, while superior hybrids are advanced for cultivar development.